The off-target effects of AID in carcinogenesis - Jiao, Junna; Lv, Zhuangwei; Wang, Yurong; Fan, Liye; Yang, Angang (Frontiers in Immunology, 2023)
Activation-induced cytidine deaminase (AID) plays a crucial role in promoting B cell diversification through somatic hypermutation (SHM) and class switch recombination (CSR). While AID is primarily associated with the physiological function of humoral immune response, it has also been linked to the initiation and progression of lymphomas. Abnormalities in AID have been shown to disrupt gene networks and signaling pathways in both B-cell and T-cell lineage lymphoblastic leukemia, although the full extent of its role in carcinogenesis remains unclear. This review proposes an alternative role for AID and explores its off-target effects in regulating tumorigenesis. In this review, we first provided an overview of the physiological function of AID and its regulation. AID plays a crucial role in promoting B cell diversification through SHM and CSR. We then discussed the off-target effects of AID, which includes inducing mutations of non-Igs, epigenetic modification, and the alternative role as a cofactor. We also explored the networks that keep AID in line. Furthermore,